Infinite Factorial Summation with Sum of the powers of 2

Calculus Level 4

S = 1 + 1 + 2 2 ! + 1 + 2 + 2 2 3 ! + 1 + 2 + 2 2 + 2 3 4 ! + \large S= 1 + \dfrac{1+2}{2!} + \dfrac{1+2+2^2}{3!} + \dfrac{1+2+2^2+2^3}{4!} + \cdots

Given that S = A e 2 + B e + C S = Ae^2 + Be + C , where A , B A,B and C C are integers, and e = lim x 0 ( 1 + x ) 1 / x 2.718 \displaystyle e= \lim_{x\to 0} (1+x)^{1/x} \approx 2.718 , find the value of A × B × C A\times B \times C .


Try more problems of this type here .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Guilherme Niedu
May 9, 2016

From geometric progression formula:

S = n = 0 2 n + 1 1 ( n + 1 ) ! \large \displaystyle S = \sum_{n=0}^{\infty} \frac{2^{n+1} - 1}{(n+1)!}

S = n = 0 2 n + 1 ( n + 1 ) ! n = 0 1 ( n + 1 ) ! \large \displaystyle S = \sum_{n=0}^{\infty} \frac{2^{n+1}}{(n+1)!} - \sum_{n=0}^{\infty} \frac{1}{(n+1)!}

Making m = n + 1 m=n+1 for both sums

S = m = 1 2 m m ! m = 1 1 m ! \large \displaystyle S = \sum_{m=1}^{\infty} \frac{2^{m}}{m!} - \sum_{m=1}^{\infty} \frac{1}{m!}

S = ( m = 0 2 m m ! 1 ) ( m = 0 1 m ! 1 ) \large \displaystyle S = \left ( \sum_{m=0}^{\infty} \frac{2^{m}}{m!} - 1 \right) - \left ( \sum_{m=0}^{\infty} \frac{1}{m!} -1 \right )

S = ( e 2 1 ) ( e 1 ) \large \displaystyle S = (e^2 - 1) - (e-1)

S = e 2 e \large \displaystyle S = e^2 - e

Thus, A = 1 , B = 1 , C = 0 A = 1, B = -1, C = 0 and their product is 0 \fbox{0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...